A low-cost system and method for acquiring small refraction seismic surveys - Dean, Tim; Nguyen, N.; Costall, A. (2019)
© 2018 SEG. The seismic refraction method has undoubted value for near-surface characterisation but its use is generally quite limited. This is often ascribed to the cost of purchasing the required equipment, often exceeding $20,000. In this paper we describe an alternate, low-cost, method for acquiring seismic refraction data. It involves the use of cheap, widely-available, open-source hardware with a total cost of less than $150, coupled with a simple, though innovative, processing method. As well as the cost of the equipment the new system also allows data to be acquired more quickly (8 minutes vs. 30 minutes for a conventional system). Although the data acquired is lower quality, due to the higher noise level, it is still sufficient for shallow applications and can be improved by stacking.